Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
the answer is B. (y+2)+y=6
since x=y+2 substitute y+2 for x in the first equation to get (y+2)+y=6
since x=y+2 substitute y+2 for x in the first equation to get (y+2)+y=6
The equation (y+2)+y = 6 shows the substitution method to solve the given system of linear equations.
What is system of linear equation?
A system of linear equations is a collection of one or more linear equations involving the same variables.
What is substitution method?
The substitution method is the algebraic method to solve simultaneous linear equations. In this method, the value of one variable from one equation is substituted in the other equation, to get the value of another variable.
According to the question
We have a system of linear equations,
x + y = 6 ...(i)
and, x = y + 2...(ii)
For finding the value of y,
substitute the value of x = y +2 in equation (i)
⇒ y +2 +y = 6
⇒ 3y + 2 = 6
⇒ 3y = 6-2
⇒ 3y = 4
⇒ y = 4/3
Hence, the equation (y+2)+y = 6 shows the substitution method to solve the given system of linear equations.
Learn more about substitution method here:
https://brainly.com/question/14619835
#SPJ2
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.